Entrepreneurship Based Financial Management Literacy Training for Tobacco Entrepreneurs in the Community in Garut Regency - Solihat, Asri; Dahlena, Alni; Maolani, Rivaldy; Safari, Shabina Meisya Andriani (Indonesian Journal of Community Empowerment (IJCE), 2025)
Reliance on traditional practices and a lack of access to entrepreneurship training further exacerbate these conditions. The lack of financial literacy among tobacco entrepreneurs makes it difficult for them to maintain financial records, manage capital, plan long-term finances, and make strategic business decisions. This dependence on traditional practices and a lack of access to entrepreneurship training further exacerbate these conditions. The activity was implemented through a participatory and applied approach, with the aim of increasing the capacity of tobacco entrepreneurs in financial management and entrepreneurship literacy. The implementation method was divided into three main stages: preparation, training, and evaluation and follow-up mentoring. The results of this community service activity can improve the managerial capacity of tobacco entrepreneurs in Garut Regency, support their business growth, and contribute positively to the local economy. Through this activity, it is hoped that entrepreneurs will not only understand financial literacy but also be able to make strategic business decisions for future business sustainability. Therefore, training on the elements of financial literacy will help participants understand the importance of financial planning, cash management, and financial reporting.